1991
DOI: 10.1007/bf00011196
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature on colonization of spring barleys by vesicular arbuscular mycorrhizal fungi

Abstract: The effects of three soil temperatures on growth of spring barleys (Hordeum vutgare L.) and on their root colonization by vesicular arbuscular mycorrhizal (VAM) fungi from agricultural soils in Montana (USA) or Syria at different inoculum concentrations were tested in soil incubators in the greenhouse. The number of mycorrhizal plants as well as the proportion and intensity of roots colonized increased with higher soil temperatures. VAM fungi from Montana, primarily Glomus macrocarpum, were cold tolerant at ll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 24 publications
0
13
1
Order By: Relevance
“…Yet, it must be borne in mind that these studies are the results of studies conducted in greenhouses. Moreover, AM morpho-species, depending on the occurrence site may express varying degrees of temperature tolerance (Grey 1991). On the other hand, soil pH and available organic carbon (%) of soil had an adverse effect on percent mycorrhizal root colonization; which in contradiction to earlier researches.…”
Section: Discussioncontrasting
confidence: 61%
“…Yet, it must be borne in mind that these studies are the results of studies conducted in greenhouses. Moreover, AM morpho-species, depending on the occurrence site may express varying degrees of temperature tolerance (Grey 1991). On the other hand, soil pH and available organic carbon (%) of soil had an adverse effect on percent mycorrhizal root colonization; which in contradiction to earlier researches.…”
Section: Discussioncontrasting
confidence: 61%
“…The abundant and diverse spore population of Glomus spp. revealed in the study indicates a good adaptation of these fungi to a wide range of soil conditions (Grey 1991;Blaszkowski 1993;Ammani et al 1994;Jansa et al 2002;Kowalczyk and Błaszkowski 2011).…”
Section: Genera Recordedmentioning
confidence: 88%
“…Specifically, temperature is among the strongest selective pressures for many species (Hochdka, 1984;Bennett et al, 1990) and is an ecological variable that affects AMF (Helgason and Fitter, 2009). There is some evidence that isolates of AMF perform best at the temperatures similar to those of their natural habitats (Schenck and Schroder, 1975;Siqueira et al, 1985;Grey, 1991), but opposing evidence indicates no local adaptation of AMF to their native climatic conditions (Lekberg and Koide, 2008;Gavito and Azc on-Aguilar, 2012). Antunes et al (2011) found that the growth of AMF isolates was not directly affected by temperature, but that isolates originating from contrasting climates consistently and differentially altered plant growth responses.…”
Section: Introductionmentioning
confidence: 95%